EVALUASI DAN PENGEMBANGAN KURIKULUM PENDIDIKAN BAHASA ARAB: ANALISIS BERBASIS MODEL CIPP - Abdurrahman Abdurrahman (Jurnal Manajemen Pendidikan, 2025)
This study aims to evaluate and formulate the direction of development of the Arabic language education curriculum using the CIPP Model (Context, Input, Process, Product) approach. This research uses a literature study method by systematically examining various scientific literature, the results of previous research, and policy documents related to the Arabic curriculum and learning. The results of the study show that in the context dimension, the Arabic curriculum still tends to be oriented towards a grammatical approach and is not fully responsive to the needs of students and contemporary educational dynamics. From the input aspect, the implementation of the curriculum is greatly influenced by the readiness of human resources, especially the pedagogical competence of teachers, the availability of contextual teaching materials, and the support of institutional facilities and policies. The process evaluation revealed that Arabic learning practices are still dominated by teacher-centered methods with the use of communicative approaches and limited learning technology. Meanwhile, in the product dimension, it was found that there was a gap between the curriculum objectives and the achievement of students' competencies, especially in applicable language skills. This study emphasizes that the development of the Arabic language education curriculum needs to be carried out comprehensively and sustainably by making CIPP evaluation as the basis for curriculum improvement, learning, and assessment systems.